Orbis Terrarum Nova et Accuratissima Tabula - Goos, Pieter, ca. 1616-1675 (Goos, Pieter ca. 1616-1675, 1661)
17th century Copper engraving handcolored with watercolor. Outline color. Mounted on cloth. Printed in top left corner in cartouche: "Orbis Terrarum Nova et Accuratissima Tabula. auctore Petro Goos." Printed in top right corner in cartouche: "Nieuwe Werelt Kaert uyt gegeven tot Amsteldam by Pieter Goos." Double-hemisphere projection with insets of the North Pole and South Pole in the lower left and right corners respectively. Of note, California is shown as an island and the northwestern portion of North America is not drawn. New Zealand and Australia are shown though Australia is marked as "Hollandia Nova." Along bottom edge, includes illustration of several allegorical figures representing the seasons with other people. Along both the right and left borders, cherubim's heads are seen blowing at the map, representing wind. Along top edge, the sun and moon are visible among clouds and small and large birds fly through the sky. The cartouche in the upper left corner is decorated by two birds and the cartouche in the upper right corner is decorated by four fish. Scale: c.a. 1:50,000,000 - 90,000,000 Pieter Goos was a cartographer, engraver, publisher, printer and printseller in Amsterdam. He was the son of another cartographer, Abraham Goos (ca. 1590-1643) (Tooley, 253). Goos was best known for his marine atlases. The style and professionalism of his work mimics the work of Visscher and Blaeu (Shirley, 456). Goos' work includes: "Lichtende Colum" (1650, 1654, 1657, 1664, 1670; English edition 1669), "Nieuwe groote zee-spiegel" (1662, 1674), "Zee Custen van Europa" (1655), "Zee Atlas (1666, 1668, 1674, 1675), "De Zee Atlas ofte Water-Wereld (1666), and "Le Grand et Noveau Miroir del Mer" (1667, 1671) (Tooley, 253). This particular map was first published in "De Zee-Atlas ofte Water-Wereld" in 1666 in Amsterdam (Wagner, entry 393). Koeman notes that "Zee Atlas" was "not a very original work" and writes that a majority of the charts included in this atlas were copied from Hendrik Doncker's "Sea-atlas" (196). Source(s): Koeman, Cornelius, ed. "Alantes Neerlandici: Bibliography of Terrestrial, Maritime, and Celestial Books, Atlases and Pilot Books Published in the Netherlands up to 1880. Volume 4." Amsterdam: Theatrum Orbis Terrarum Ltd., 1970. Shirley, Rodney W. "The Mapping of the World: Early Printed World Maps 1472-1700. Riverside, CT: Early World Press Ltd., 2001. Tooley, Ronald Vere. "Tooley's Dictionary of Mapmakers." Hertfordshire: Map Collector Publications Limited, 1979. Wagner, Henry R. "The Cartography of the Northwest Coast of America to the year 1800 Volume 2." Berkeley: University of California Press, 1937.